The new universal order : 5 letters in English and Italian to the Presidents Roosevelt and Truman = Il nuovo ordine universale : 5 lettere in inglese e italiano ai Presidenti Roosevelt e Truman - Pucelli, Rodolfo (New York : Vincenzo Grassi, 1946)
Bibliotheek Camille Huysmans
Engels
Italiaans
Brochure
Keywords: pacifisme; internationale samenwerking